2002
DOI: 10.1007/s00894-002-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of human CCR2b and primate CCR2b by molecular modeling and molecular dynamics simulation

Abstract: CCR2b, a chemokine receptor for MCP-1, -2, -3, -4, plays an important role in a variety of diseases involving infection, inflammation, and/or injury, as well as being a coreceptor for HIV-1 infection. Two models of human CCR2b (hCCR2b) were generated by homology modeling and 1 ns restrained molecular dynamics (MD) simulation. In one only C113-C190 forms a disulfide bond (SS model); in another the potential C32-C277 disulfide bond was formed (2SS model). Analysis of the structures and averaged displacements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Previously homology models of CCR2 were developed using the traditionally used bovine rhodopsin and the recently reported β 2 -adrenergic receptors as templates. 21,[54][55][56] In this study we used the recently reported CXCR4 (PDB code: 3ODU) as a template and modeling was done because of the non-availability of crystal structure. A molecular docking study was then performed with 16b of 4AAC against the proposed binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Previously homology models of CCR2 were developed using the traditionally used bovine rhodopsin and the recently reported β 2 -adrenergic receptors as templates. 21,[54][55][56] In this study we used the recently reported CXCR4 (PDB code: 3ODU) as a template and modeling was done because of the non-availability of crystal structure. A molecular docking study was then performed with 16b of 4AAC against the proposed binding site.…”
Section: Discussionmentioning
confidence: 99%
“…al. reported a modeled structure for CCR2 (PDB code: 1KP1) and it is publicly available [22] . The alignment used for the model development and the model obtained after MD analysis is shown in Fig.…”
Section: Homology Modeling Of Ccr2 and Ccr5mentioning
confidence: 99%
“…Furthermore, the residues shown in color under the query sequence but not in the template sequence are identical to the residues present in bovine rhodopsin. Bovine rhodopsin was used as a template for some previously reported homology models of CCR2 (Berkhout et al, 2003;Mirzadegan et al, 2000;Shi et al, 2002 identity between bovine rhodopsin and CCR2 is 21% while between human b 2 -adrenoceptor and CCR2 receptor is 24%.…”
Section: Sequence Alignmentmentioning
confidence: 99%
“…Shi et al also developed two homology models of CCR2b receptor taking bovine rhodopsin as the template. In one of the models, there was only one disulfide bond (1KAD) while in the other (1KP1) there are two disulfide bonds (Shi et al, 2002). Hence, one can develop a homology model of human CCR2 receptor with the help of newly available crystal structures of GPCRs such as human b 2 -adrenoceptor (2007), human A2A adenosine receptor (2008), and turkey b 1 -adrenoceptor (2008).…”
Section: Introductionmentioning
confidence: 99%